Optimizing Material and Technology Selection for Cost-Effective Equipment Performance - Valerii Netrebko; Vadym Shalomieiev; Serhii Sheiko; Olexandr Shapurov; Oleksii Hrechanyi; Valentyna Tretiak (Challenges and Issues of Modern Science)
Purpose. To optimize criteria for evaluating the implementation of wear-resistant materials to reduce production costs and equipment downtime. Design / Method / Approach. The study employed an analytical review of publications, spectral and metallographic analysis of alloys, a gravimetric method for assessing wear resistance, and heat treatment to enhance it. Findings. An analysis of challenges in developing materials for mining, metallurgical, and construction equipment was conducted. It was established that component service life must align with equipment maintenance schedules. New materials with enhanced wear resistance may be economically unviable due to high costs or inability to realize durability benefits. A balance between cost and service life is achieved by analyzing operating conditions and defining material and technology requirements. Theoretical Implications. The study expands knowledge on reducing production costs by identifying criteria for the effective implementation of materials and technologies. Practical Implications. A multi-criteria analysis is proposed for adopting new materials and technologies in the production of components for mining, metallurgical, and construction equipment, reducing costs and downtime. Originality / Value. The methodology uniquely optimizes material selection by aligning component durability with maintenance schedules, minimizing downtime. Its innovative alloy development resolves conflicting material requirements, enhancing production efficiency. Research Limitations / Future Research. Limitations include a focus on specific materials; future research should explore a broader range of materials and conditions. Article Type. Empirical.